(untitled) (Intellectual Inception: A Multidisciplinary Research Journal of Bhojpur Campus, 2023)
This paper explores the place of spirituality in yoga from Vedic period to the present. Linking to its Vedic origin, an attempt is made to show spirituality as the key aspect of yoga that has nearly been forgotten in modern days. Its basic philosophy is to control our ever-fleeting mind dissociating it from materiality. Beginning from physical activities, it moves to mental ones and ends in spirituality that is the realization of the essence. The objective of this paper is to show how spirituality, the most essential aspect of yoga, has been forgotten in modern time. Referencing from different ancient scriptures and associating with different religions, this paper points out that spirituality is the essence of yoga practice and this aspect is dimmed and limited to physical activities at present. It is commoditized and detached from its spiritual association. Such activities have destroyed the originality of yoga. Following qualitative research design, this paper uses critical, analytical and interpretative methods for interpreting textual data to justify the claim. Critiquing the present trend of detaching yoga from spirituality, I argue for the continuity of yoga with its philosophical base. Otherwise, yoga will turn into just a form of physical exercise for physical fitness.